The MADS-Box Transcription Factor EjAGL65 Controls Loquat Flesh Lignification via Direct Transcriptional Inhibition of EjMYB8 - Ge, Hang; Shi, Yan-na; Zhang, Meng-xue; Li, Xian; Yin, Xue-ren; Chen, Kun-song (Frontiers in Plant Science, 2021)
Loquat fruit accumulates lignin in its flesh when undergoing chilling injury during postharvest storage, making it a suitable model for the study of flesh lignification. Transcriptional regulation of lignin biosynthesis is principally controlled by the NAC-MYB transcriptional cascade in model plants. Previous research has demonstrated that EjMYB8 activates lignin biosynthesis through direct interaction with the promoter of Ej4CL1. However, the classic NAC-MYB gene regulation network has not been established. Here, the MADS-box gene EjAGL65 was discovered by screening a cDNA library using the EjMYB8 promoter as bait in yeast. A phylogenetic analysis and structural comparisons revealed that EjAGL65 belongs to the Mδ subgroup of the MADS-box family, whose members have not been reported as being involved in the regulation of lignin deposition. EjAGL65 transcription was downregulated at 0°C compared to 5°C, indicating a negative correlation with the change of lignin content. A dual-luciferase assay indicated that EjAGL65 is capable of inhibiting the promoter activity of EjMYB8 in vivo. These results showed that the Mδ MADS-box gene EjAGL65 transcriptionally regulates EjMYB8 during postharvest chilling induced flesh lignification, which differs from the classical regulation model of lignin biosynthesis that has been illustrated for developmental lignin accumulation.